Síndrome de Seckel, Dos Casos en una Familia Colombiana (2010)
Seckel syndrome is an infrequent autosomic recessive genetic disorder. It is characterized by short stature, mental retardation and a typical facies. Nearly 10 families have been reported with two or more affected members.This paper reports two sisters, daughters of non-related parents. The mother presented bilateral fissurate lip. The main traits of this syndrome are highlighted through a literature review.